Strobilanthes orbiculata (Acanthaceae) a new species and notes on S. matthewiana from the southern Western Ghats, India - Thomas, Sinjumol; Mani, Bince; Britto, Susai John (Phytotaxa, 2018)
A new species Strobilanthes orbiculata is described from the southern parts of the Western Ghats, India. It is a semelparous species found in the shola forests in Vattavada and Kundala in Idukki district of Kerala. Notes on pollen morphology, distribution, phenology, conservation status and photographic illustrations are given. Moreover, a short note on a narrow endemic taxon Strobilanthes matthewiana is also provided.